Pelatihan Pembuatan Website Untuk Peningkatan Publikasi Desa Wisata Di Desa Gebang, Kec. Padang Cermin, Kab. Pesawaran - Ridho Sholehurrohman; Igit Sabda Ilman; Yunda Heningtyas; Muhaqiqin Muhaqiqin; Rahman Taufiq; Irwan Adi Pribadi (Universitas Teknokrat Indonesia, 2023)
Tourism is one of the rapidly growing industries in Indonesia and has proven to contribute a large income. Tourism will continue to grow in line with the development of industrialization and changes in people's lifestyles, who increasingly have the ability to travel and have more time to do so, especially in Indonesia. Gebang village is one of the villages located in Padang Cermin district, Pesawaran regency. Gebang village is a village with a large tourism object and mangrove conservation. This condition is supported by the availability of observation tracks along the coast and even entering the mangrove forest area, making this area one of the important natural/educational tourism destinations in Lampung province. By combining the use of technology and information systems, it is expected that Gebang village can display public information that serves as a promotional medium to introduce the profile and objects of Gebang village tourism. The village website can also be used as a portal for an integrated database system. Based on the assessment of the Pesawaran Regency government, Gebang village has sufficient resource readiness to utilize technology and information systems such as a website. This PKM (Community Service Program) activity aims to transfer knowledge in implementing and managing the Gebang Village Tourism website.